2021
DOI: 10.1186/s12872-021-01933-7
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of long-term clinical outcomes by successful PCI in the very elderly women with ACS

Abstract: Background Whether very elderly women with acute coronary syndromes (ACS) should receive aggressive percutaneous coronary intervention (PCI) is still controversial. We assessed the effectiveness and long-term clinical outcomes of successful PCI in this population and identified prognostic factors which might contribute to the incidence of major adverse cardiovascular and cerebrovascular events (MACCE) in the very elderly female PCI cohort. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
4
3
Order By: Relevance
“…A large number of studies showed that there was a negative correlation between levels of knowledge and age with older people having being less knowledgeable than their younger counterparts. 1,5,7,9,11,15,16 However, there was no association that was found between age and dependent variable in our study.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…A large number of studies showed that there was a negative correlation between levels of knowledge and age with older people having being less knowledgeable than their younger counterparts. 1,5,7,9,11,15,16 However, there was no association that was found between age and dependent variable in our study.…”
Section: Discussioncontrasting
confidence: 84%
“…At present, after stent the recurrence rate is well below 10%.With these improvements in the overall levels of safety and effectiveness of PCI, the number of procedures being carried out has seen an exponential increase with more than 90% of all PCI procedures involving at least one coronary stent. 4,5 It was in 1977 that the very first coronary balloon angioplasty was carried out by Andreas Gruentzigusing. Since the first time, this procedure has grown in use and been developed progressively with the advances in technology.…”
Section: Introductionmentioning
confidence: 99%
“…Those figures were better than those noticed in the study fulfilled by Kocayigit et al [18] in which 8.9% of primary PCI patients suffered ischaemic stroke. However, CVS figure (3.4%) in the study done by Wang et al [19] may be considered better than its counterpart in our study as its population was very elderly women >80 years of age.…”
Section: Discussioncontrasting
confidence: 64%
“…This may be explained by the longest follow-up period ranging from 4 month to 2 years. [19] in which hospital stay ranged from six to ten days, with 7 days in average. This may be explained by the lower frequency of inhospital complications recorded in the current study, and the relative shortage of CCU beds indicating a more rapid cycle of admission and discharge of patients.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the most commonly used clinical diagnosis methods are color Doppler ultrasound diagnosis, CT, MRI diagnosis, and blood index testing, among which color Doppler ultrasound diagnosis is the simplest and fastest diagnosis method. Blood index testing facilitates the determination of related diseases by evaluation of the expression level of specific blood indices, which is associated with more accurate diagnostic results [21][22][23].…”
Section: Discussionmentioning
confidence: 99%